Cytogenomic evaluation of regenerated Aralia elata using PLOP-FISH and flow cytometry - Eliazar Alumbro Peniton; Hong Thi Nguyen; Nomar Espinosa Waminal; Tae-Jin Yang; Hyun Hee Kim (Scientific Reports)
Abstract Aralia elata is closely related to Panax ginseng and contains high levels of saponins and other medicinal compounds. Successful A. elata micropropagation is commercially significant; however, the genomic stability of tissue culture-derived regenerants is unclear. In this study, callus-derived regenerated A. elata plants were obtained, and their cytogenomic constitutions were assessed. Using RepeatExplorer, pre-labeled oligonucleotide probes (PLOPs) were developed with newly mined tandem repeats from < 1× NGS whole-genome short reads, fluorescence in situ hybridization (FISH) was performed using six repeat probes, including three universal PLOPs, and genomic DNA content was estimated using flow cytometry. Regenerated A. elata plants (50) exhibited consistent ploidy, repeat distribution, and genome sizes compared with those exhibited by the mother plant. Six repeat probes were detected using FISH. Tandem repeat AeTR49 was identified as an excellent cytogenetic marker for homologous chromosomes, and AeTR161 and AeTR178 were localized in the centromeric and telomeric sections, respectively. Genomic DNA content (2C) was estimated at 2.46 ± 0.04 pg in the mother plant and 2.41 ± 0.05 pg in regenerated plants, with no significant variations in genome size or chromosome length. These results demonstrate that cytogenomics can be used to effectively evaluate chromosome-level genomic stability in regenerated A. elata plants.